Pengaruh Program TV Edukasi X-Sains Sebagai Sumber Belajar Terhadap Hasil Belajar IPA Siswa Kelas IV SDN Pakis V Surabaya - Gultom, Rissanti Ayudita Oktaviery; Yuliana, Leni; Setiyawan, Hery (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
Educational Television Program, such as X-Science Educational TV Program, is one of the government's innovations in providing educational programs for the public. This study aimed to describe the effect of the X-Science Education TV program on the fourth-grade students' science learning outcomes at SDN Pakis V Surabaya. The study was an experimental design with a nonequivalent control group design. The study subject was fourth-grade students at SDN Pakis V Surabaya. The study instrument was a pre-and post-test using the google form application. The data collection technique was the learning outcome test. The data analysis technique was an independent sample T-test using IBM SPSS 24 application. The test analysis results obtained from the independent sample T-test showed t count > t table value, 2.298 > 2.024. Hence, H0 was rejected and Ha was accepted. The significance value (2-tailed) was 0.027 < 0.05, so there was a significant difference between the control and experimental groups' learning outcomes. The amount effect of the X-Science TV Educational Program on science learning in fourth-grade students at SDN Pakis V Surabaya was 31.06%. Based on the percentage gain, the X-Science TV Education Program positively affects science learning outcomes for fourth-grade students at SDN Pakis V Surabaya.